A rapid in vitro assay for evaluating the effects of acetylcholinesterase inhibitors and reactivators in the rat basolateral amygdala - Thinschmidt, Jeffrey S.; Harden, Scott W.; King, Michael A.; Talton, James D.; Frazier, Charles J. (Frontiers in Cellular Neuroscience, 2022)
We established a novel brain slice assay to test the ability of acetylcholinesterase (AChE) reactivators to prevent ACh-induced M1 muscarinic acetylcholine receptor (mAChR) dependent hyperexcitability observed after exposure to the organophosphate (OP)-based AChE inhibitor and sarin surrogate 4-nitrophenyl isopropyl methylphosphonate (NIMP). Whole-cell patch clamp recordings were used to evaluate the response of pyramidal neurons in the rat basolateral amygdala (BLA) to brief (1 min) bath application of ACh (100 μM), either in control conditions, or after exposure to NIMP ± an AChE reactivator. Bath application of ACh produced atropine- and pirenzepine-sensitive inward currents in voltage clamped BLA pyramidal neurons, and increased the frequency of spontaneous EPSCs, suggesting robust activation of M1 mAChRs. Responses to ACh were increased ~3–5 fold in slices that had been preincubated in NIMP, and these effects were reversed in a concentration dependent manner by exposure to a commercially available AChE reactivator. The current work outlines a simple assay that can be used to evaluate the efficacy of both known and novel AChE reactivators in an area of the limbic system that likely contributes to seizures after acute exposure to OP-based AChE inhibitors.